Legal Protection for Health Workers Against Risk of Covid-19 Transmission in Hospital Emergency Installation Services dr. H. Soewondo, Kendal Regency - Ertanto, Widiyo; Yustina, Endang Wahyati; Suroto, Val (Universitas Katolik Soegijapranata Semarang, 2022)
Abstract: RSUD dr. H. Soewono Kendal is one of the health service units designated by the Government as a Covid-19 referral hospital for the people of Kendal so that medical workers and health workers on duty at Dr H.Soewondo Kendal Hospital, especially in the emergency room, must make physical contact and have close contact with suspected COVID-19 patients and those who have tested positive for COVID-19. This causes the risk of transmission of Covid-19 to health workers to be great, so there is a need for legal protection for medical workers and health workers who work in the emergency room as one of the main entry points for patients at the hospital.This research is a sociological juridical research with a descriptive-analytical research specification. This study uses primary data and secondary data. Data collection in this study was carried out through field studies and literature studies to obtain the necessary data. The data analysis method used is qualitative.The implementation of legal protection for health workers in the emergency room against the risk of transmission of Covid-19 has been well implemented through preventive legal protection in the form of screening, triage, the establishment of a 3M task force, the existence of various internal regulations related to PPI during a pandemic, provision of health insurance and covid-19 vaccination, repressive legal protection is carried out by providing health services for exposed health workers as well as providing incentives and death benefits. There are factors that hinder and support its implementation, namely social factors, juridical factors and technical factors. As a result of these factors, patient fluctuations still occur in the ED because the inhibiting factor causes the risk of transmission to remain because of this.Keywords: legal protection, pandemic, covid-19, health workers, emergency room Abstrak: RSUD dr.H. Soewono Kendal merupakan salah satu unit pelayanan kesehatan yang ditunjuk oleh Pemerintah sebagai rumah sakit rujukan covid-19 bagi masyarakat Kendal sehingga tenaga medis dan tenaga kesehatan yang bertugas di RSUD dr.H.Soewondo Kendal khususnya di ruang IGD harus melakukan kontak fisik dan kontak erat dengan pasien terduga covid-19 maupun yang sudah positif covid-19. Hal ini menyebabkan risiko penularan covid-19 kepada petugas kesehatan menjadi besar, sehingga perlu adanya pelindungan hukum bagi tenaga medis dan tenaga kesehatan yang bertugas di ruang IGD sebagai salah satu pintu utama masuknya pasien di rumah sakit.Penelitian ini merupakan penelitian yuridis sosiologis dengan spesifikasi penelitian desktiptif-analitis. Penelitian ini menggunakan data primer dan data sekunder. Pengumpulan data pada penelitian ini dilakukan melalui studi lapangan dan studi kepustakaan untuk memperoleh data yang diperlukan. Metode analisis data yang digunakan adalah kualitatif.Pelaksanaan pelindungan hukum bagi tenaga kesehatan di IGD terhadap risiko penularan covid-19 sudah dilaksanakan dengan baik melalui pelindungan hukum preventif berupa skrining, triase, pembentukan satgas 3 M, adanya berbagai peraturan internal terkait PPI di masa pandemi, pemberian asuransi kesehatan dan vaksinasi covid-19, pelindungan hukum represif dilakukan dengan pemberian layanan kesehatan bagi tenaga kesehatan yang terpapar serta pemberian insentif dan santunan kematian. Terdapat faktor yang menghambat dan mendukung pelaksanaannya yaitu faktor sosial, faktor yuridis dan faktor teknis. Akibat faktor-faktor tersebut adalah di IGD masih terjadi penumpukan pasien karena faktor penghambat menyebabkan risiko penularan tetap masih ada karena hal tersebut.Kata kunci: pelindungan hukum, pandemi, covid-19, tenaga kesehatan, IGD